Tindak Tutur Ilokusi dalam Film Animasi Upin dan Ipin Episode â€œSeronoknya Wisata Airâ€ serta Implikasinya Terhadap Pendidikan Karakter Anak - Lestari, Bini (ESTETIK : Jurnal Bahasa Indonesia, 2019)
This study aims to describe the forms of illocutionary speech acts in the animated film Upin & Ipin in the series "Seronoknya Wisata Air". In addition, this study also describes the form of character education contained in the animated film. Furthermore, this study uses a qualitative method with a descriptive approach. The data source in this study obtained conversations in the animated film Upin & Ipin obtained from Television. Data collection techniques in this study used the note taking technique, by noting every conversation that contains illocutionary speech acts. The data validity technique in this research is in the form of theory triangulation, data analysis using interactive analysis. The results of the study show that in the animated film Upin & Ipin the series of "Water Tourism" contains illocutionary acts. For example assertive, directive and expressive. In this study, researchers also found the value of character education contained in the Upin & Ipin animated film "Seronoknya Wisata Air", for example disciplinary value, creative value, value of achievement and friendly values. Keywords: Illocutionary Speech Acts, Upin & Ipin Animated Film, Character Education